2017
DOI: 10.1016/j.joca.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and evidence synthesis of qualitative studies to identify primary care clinicians' barriers and enablers to the management of osteoarthritis

Abstract: PROSPERO (http://www.crd.york.ac.uk/PROSPERO) [4/11/2015, CRD42015027543].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
186
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(204 citation statements)
references
References 47 publications
12
186
3
Order By: Relevance
“…Egerton et al () (Egerton et al, ) and many others have reported the perception that ‘OA is not that serious’ and that ‘personal beliefs are at odds with providing recommended practice’. A body of literature suggests that OA is a low priority to both HCPs and patients, and, that HCPs' personal beliefs do not always align with recommended guidelines (Egerton et al, , Paskins, Sanders, & Hassell, , Paskins, Sanders, & Hassell, , Thomas, Moore, Roddy, & Peat, , Jinks, Ong, & Richardson, ). In addition, findings illustrated how self‐management was not viewed as core business by some GPs and because the condition didn't align to pay‐for‐performance targets, and implementation was reported not to provide any benefits to the practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Egerton et al () (Egerton et al, ) and many others have reported the perception that ‘OA is not that serious’ and that ‘personal beliefs are at odds with providing recommended practice’. A body of literature suggests that OA is a low priority to both HCPs and patients, and, that HCPs' personal beliefs do not always align with recommended guidelines (Egerton et al, , Paskins, Sanders, & Hassell, , Paskins, Sanders, & Hassell, , Thomas, Moore, Roddy, & Peat, , Jinks, Ong, & Richardson, ). In addition, findings illustrated how self‐management was not viewed as core business by some GPs and because the condition didn't align to pay‐for‐performance targets, and implementation was reported not to provide any benefits to the practice.…”
Section: Discussionmentioning
confidence: 99%
“…Research exploring the process of implementing evidence‐based guidelines is required to provide insights into the practical, real‐world issues encountered and to develop targeted implementation strategies (Allen et al, ). Previous evidence syntheses have described clinicians' views of the barriers and enablers of the management of OA (Egerton, Diamond, Buchbinder, Bennell, & Slade, ) and factors affecting implementation more broadly across a range of conditions in primary care (Lau et al, ). The perceived barriers to implementation of best practice guidelines for OA across hospital and community settings have also been explored (Brand & Cox, ), however, to date, no study has synthesized the experiences of implementing evidence‐based guidelines for OA in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hofstede et al found similar barriers for referral to non‐surgical treatment for OA patients in orthopaedic practice (Hofstede et al, ). Egerton et al described in a systematic review similar barriers to the management of osteoarthritis in primary care GPs: GPs tend to trivialize the problem and believe OA to be inevitable and lower priority than other health conditions which may lead to under management of the condition; a lack of knowledge regarding OA guidelines; clinicians' perceptions about the disease, patient adherence and the treatment effectiveness may all lead to variable practice at odds with the recommendations (Egerton, Diamond, Buchbinder, Bennell, & Slade, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example a systematic review by Hendry, Snowden, and Brown (2017) found that mental health nurses' conservative attitudes about clients' sexual health meant nurses avoided conversations about sexuality. Similarly, another systematic review identified that primary care clinicians' personal beliefs about osteoarthritis meant they were less likely to recommended evidence-based treatments (Egerton, Diamond, Buchbinder, Bennell, & Slade, 2017).…”
Section: Discussionmentioning
confidence: 99%